2014
DOI: 10.1111/bor.12092
|View full text |Cite
|
Sign up to set email alerts
|

Holocene salt‐marsh sedimentary infilling and relative sea‐level changes in West Brittany (France) using foraminifera‐based transfer functions

Abstract: International audienceIn order to reconstruct the former sea-levels and to better characterize the history of Holocene salt-marsh sedimentary infillings in West Brittany (western France), local foraminifera-based transfer functions were developed using Weighted-Average-Partial-Least-Squares (WA-PLS) regression, based on a modern dataset of 26 and 51 surface samples obtained from salt-marshes in both the bay of Tressseny and the bay of Brest. Fifty cores were retrieved from Tresseny, Porzguen, Troaon and Arun s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(73 citation statements)
references
References 89 publications
2
70
1
Order By: Relevance
“…Much of this coastal population is directly or indirectly affected by coastal flood risks, even as such risks might be mitigated by forward-thinking coastal wetland management and preservation [7]. Stratigraphic and paleoecological evidence documents that coastal wetlands have adapted to marine transgressions and regressions throughout the Holocene [8][9][10][11][12][13]. Hence, coastal wetlands appear to be self-sustaining ecosystems despite human, climate, and sea level impacts.…”
Section: Coastal Wetland Occurrence and Valuementioning
confidence: 99%
“…Much of this coastal population is directly or indirectly affected by coastal flood risks, even as such risks might be mitigated by forward-thinking coastal wetland management and preservation [7]. Stratigraphic and paleoecological evidence documents that coastal wetlands have adapted to marine transgressions and regressions throughout the Holocene [8][9][10][11][12][13]. Hence, coastal wetlands appear to be self-sustaining ecosystems despite human, climate, and sea level impacts.…”
Section: Coastal Wetland Occurrence and Valuementioning
confidence: 99%
“…The first recorded assemblage is characterized by high percentages of non-calcareous taxa (Trochammina inflata and Jadammina macrescens), while the second type of foraminiferal assemblage is characterized by the dominance of calcareous taxa (Astergerinata mamilla, Haynesina germanica, Elphidium williamsoni, and Lobatula lobatula). From an ecological point of view, it has already been shown that non-calcareous species dominate in the upper part of the salt marsh in Brittany (Rossi et al, 2011;Stéphan et al, 2015) while calcareous foraminifera dominate in sub-tidal, tidal, and marine environments (Liu and Fearn, 1993;Collins et al, 1999;Scott et al, 2001;Murray, 2006). Even if the stratigraphy of GL1 is not robust enough, this sediment sequence is evidence that the downstream part of the Guidel marsh was submitted to continuous marine influences over the last 7000 cal BP (Fernane, 2014) with a high tide level close to −7 m NGF (Goslin et al, 2013;Goslin, 2014).…”
Section: Forcing Factors Responsible For Human Settlement and Departumentioning
confidence: 99%
“…1 mm/yr after the inflection at ca. 6 ka6364 while reconstructions from the western Netherlands document greater rates (8 m of sea-level rise after 7 ka) without a clear inflection point but a continuous attenuation rate. Goslin et al 65.…”
Section: Discussionmentioning
confidence: 94%